Mycoplasma bovis-polyarthritis and pneumonia in grazing beef steers: outbreak in Buenos Aires province - Acuña, Yamila (2021)
Mycoplasma bovis-polyarthritis and pneumonia in grazing beef steers: outbreak in Buenos Aires province Poliartritis y neumonía por Mycoplasma bovis en novillos en pastoreo: brote en la provincia de Buenos Aires Mycoplasma spp. infection causes different clinical diseases in livestock. In cattle, infection with Mycoplasma bovis usually is clinically manifested with arthritis, mastitis, pneumonia and/or otitis. This paper describes an outbreak of polyarthritis and pneumonia caused by M. bovis in grazing steers in Buenos Aires province, scarcely reported in the region. Clinical and pathological findings were recorded. Three 1-year-old steers were euthanized and post mortem examined. Tissue samples were collected for histopathology and bacteriological analysis. Different degrees of lameness were observed in 4.6% of the herd of 1000 steers. Mild respiratory signs were observed in half of the lame animals. Macroscopically, polyarthritis was present in different joints of the hind and front limbs, characterized by the presence of severe caseous tenosynovitis. In addition, multiple foci of different extension with caseous content were observed in the pulmonary parenchyma. Mycoplasma spp. was isolated and M. bovis DNA was amplified from articular content and lungs of all three animals. This clinical presentation has not been frequently reported in the region, particularly in grazing beef cattle.